Apolipoprotein E genotype does not influence the risk of symptomatic hemorrhage in acute ischemic stroke. (June 2021) - Tábuas-Pereira, Miguel; Galego, Orlando; Almeida, Maria Rosário; Tomás, José; Félix-Morais, Ricardo; Silva, Fernando; Rodrigues, Bruno; Cordeiro, Gustavo; Sargento-Freitas, João
Highlights: Apolipoprotein E gene polymorphism ε4 is associated with lobar intracranial hemorrhages. Apolipoprotein E gene polymorphism ε2 also predisposes to changes in the blood vessels and white matter changes. We found no association between APOE polymorphisms and hemorrhagic transformation following thrombolysis. Abstract: Background: APOE ε4 is independently associated with lobar intracranial hemorrhages (ICH). Although the ε4 allele enhances amyloid deposition in blood vessels, the ε2 allele predisposes to vasculopathic changes leading to rupture of amyloid laden vessels. Thus, ε4 and ε2 carriers might have increased susceptibility to ICH. We aimed to study the impact of the apolipoprotein E alleles in the development of symptomatic ICH (sICH). Methods: We included 384 consecutive ischemic anterior circulation stroke patients submitted to thrombolysis between January 2014 and March 2016. Admission CT-scans were reviewed to calculate the ASPECTS. Patients were followed for up to at least 6 months post-stroke or until death. Outcome was development of sICH, defined according to the ECASS III. Results: Considering APOE genotyping, three patients had ε2/ε2, four had ε2/ε4, 38 had ε2/ε3, 284 had ε3/ε3, 51 had ε3/ε4 and four had ε4/ε4. sICH was associated with sex and diabetes. In multivariate analysis, sICH was not associated with carrying one or more ε4 alleles (OR: 0.483, 95%CI = [0.059, 3.939], p = 0.497) nor with carrying one or more ε2 alleles (OR: 1.369, 95%CI = [0.278, 6.734], p = 0.699). Conclusion: No association was found between APOE genotype and the development of symptomatic intracranial hemorrhage.